Recurrent hyponatremia due to syndrome of inappropriate antidiuresis after traumatic brain injury: two case reports - Petria, Iulia; Indirli, Rita; Mantovani, Beatrice; Lanzi, Valeria; Mantovani, Giovanna; Ferrante, Emanuele (Frontiers in Endocrinology, 2025)
BackgroundTransient hyponatremia due to syndrome of inappropriate antidiuresis (SIAD) is a frequent (20-50%) complication of traumatic brain injury (TBI), but it rarely persists or recurs. There are only few published reports of patients suffering from non-transient hyponatremia due to chronic SIAD after TBI. We report two more cases with this condition.Case 1A 36-year-old woman suffering from major depression and treated with olanzapine reported severe TBI after a severe fall. Following head injury, she developed severe hyponatremia, which was managed with fluid restriction and salt supplementation. Upon hospital discharge, 7 months after trauma, mild hyponatremia was still reported (Na 134 mmol/L), which dropped to severe hyponatremia in a week despite continuation of treatment, and spontaneously returned to normal. Two months later, the patient presented one more episode of moderate hyponatremia without clear triggering events. Pituitary hormones were normal and urinary sodium and urinary and plasma osmolality supported the diagnosis of SIAD. Therefore, tolvaptan 7.5 mg daily was started, with sustained normalization of sodium levels. When olanzapine was stopped, discontinuation of tolvaptan was attempted. However, serum sodium dropped again and tolvaptan had to be resumed, with natremia remaining within normal range at follow-up. Consistently, olanzapine-related hyponatremia could be ruled out and post-traumatic SIAD confirmed.Case 2A 37-year-old man experienced TBI with diffuse axonal injury falling during a mountain trip. Over the following year, he presented two episodes of tonic-clonic seizures accompanied by the biochemical finding of moderate-severe hyponatremia. Hyponatremia resolved following hypertonic (3% NaCl) saline infusion, and valproate treatment was started after the second episode. In the following outpatient visits, a progressive decrease of serum sodium from 141 mmol/L to 132 mmol/L was observed, with other tests consistent with SIAD. Therefore, considering the high risk of recurrent seizures as well as the concomitant treatment with valproate, tolvaptan 7.5 mg every other day was started and normal sodium levels have been maintained since then.ConclusionsWe report two cases of recurrent SIAD following TBI, with multiple hyponatremic episodes after initial presentation. This highlights the importance of long-term follow-up of electrolyte abnormalities after head injury.